PENDIDIKAN SENI RUPA DI INDONESIA: SEJARAH, PERAN DAN TANTANGAN MASA DEPAN - awalini, Tika; Handayaningrum, Warih; Suryandoko, Welly (Universitas Pendidikan Ganesha, 2023)
Art education in Indonesia has an important role in forming a young generation who is creative, cultured, and cares about local and global art and culture. This includes cultural identity, character building, and creativity, as well as contributions to empowering the creative economy that need special attention from the government. This study aims to find out (1) the history of art education in Indonesia, (2) the role of art education, and (3) the hopes and challenges associated with the future of art education in the world of education in Indonesia. This research was written using the library research method, which uses a literature review analysis approach taken from articles and books both online and offline. The results of this study are that art education in Indonesia has a long history and was once an important subject in the Indonesian education curriculum. Art education, especially fine arts, has a major contribution to individual development, including emotional, mental, creative, social, physical and also aesthetics. Creativity is an important and influential aspect in human life. Fine arts education is one of the lighters that can be used as the vehicle and the most appropriate way to prepare the nation's creative next generation. The attention of the government and all stage holders in making policies is urgently needed so that the essence of art education which contains various benefits can have an impact on the next generation of the nation. Keywords : Art education, history, roles and challenges. Abstrak Pendidikan seni di Indonesia memiliki peran penting dalam membentuk generasi muda yang kreatif, berbudaya, dan peduli terhadap seni dan budaya lokal serta global. Hal tersebut mencakup identitas budaya, pembentukan karakter, dan kreativitas, serta kontribusi pada pemberdayaan ekonomi kreatif yang perlu mendapatkan perhatian khusus oleh pemerintah. Penelitian ini bertujuan untuk mengetahui (1) sejarah dari pendidikan seni rupa yang ada di Indonesia, (2) peran dari pendidikan seni rupa, serta (3) harapan dan tantangan yang di terkait dengan masa depan pendidikan seni rupa dalam dunia pendidikan di Indonesia. Penelitian ini ditulis menggunakan metode library research, yaitu menggunakan pendekatan analisis kajian pustaka yang diambil dari artikel dan buku baik secara online ataupun offline. Hasil dari penelitian ini adalah pendidikan seni rupa di Indonesia memiliki sejarah panjang dan sempat menjadi mata pelajaran penting di kurikulum pendidikan Indonesia. Pendidikan seni khususnya seni rupa memiliki kontribusi besar terhadap perkembangan individu antara lain emosi, mental, kreativitas, sosial, fisik dan juga estetika. Kreativitas menjadi salah satu aspek penting dan berpengaruh dalam kehidupan manusia. Pendidikan seni rupa menjadi salah satu pemantik yang dapat digunakan sebagai wahana dan cara yang paling tepat untuk menyiapkan generasi penerus bangsa yang kreatif. Perhatian dari pemerintah dan semua stage holder dalam membuat kebijakan sangat dibutuhkan agar esensi pendidikan seni rupa yang mengandung berbagai manfaat dapat berdampak bagi generasi penerus bangsa.